Pendampingan Identifikasi Potensi Untuk Membentuk Usaha Wisata Adventuring di Gunung Puntang Berdasarkan Community Base - Hutahaean, Erik Saut H; Khasanah, Fata Nidaul; Untari, Dhian Tyas; Hidarsah, Ida; Fahrudin, Adi; Perdini, Tiara Anggita; Mulyanto, Erwan; Saputra, Farhan (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2023)
Mount Puntang has a lot of potential to be used as a place for development and improvement of the quality of life of the people living around it. One of them is tourism potential. However, the situation on the ground raises several obstacles experienced by the community to develop tourism businesses. To be able to identify the need to overcome obstacles, three activities were designed in this activity. The activities carried out are knowledge transfer, focus group discussion, and field search. This activity involves the community who are activists in the maintenance and development of the potential of Mount Puntang from Cempaka Mulya village, Bandung Regency. The activists in question are activists of the puntang mountain brotherhood, puntang lestari cooperatives, and tourism observer communities. Through these three activities, results were obtained; Mount Puntang has unique potential that can be utilized for the improvement and development of people's lives. Adventuring tourism business is a positive field, however, it requires the establishment of institutional legality to be able to operate community-based tourism businessess.